SISTEM INFORMASI BUKU TAMU MENGGUNAKAN QR CODE BERBASIS WEB PADA BIRO ORGANISASI SETDA PROVINSI SUMATERA SELATAN - Fendri Martadinata (jurnal kesehatan terapan sains dan teknologi, 2024)
Abstract The use of information technology to become part of government governance, as the need for accurate and fast information availability increases. The organizational bureau has the task of providing administrative services in carrying out regional government tasks and preparing materials for coordinating the formulation of policies for implementing the tasks and functions of regional apparatus in the organizational field. So far, the Organization Bureau for recording guest books still uses manual guest books using paper media. With manual recording, the system for searching guest data is not fast and the guest book is often damaged. By using a guest book information system using a web-based QR code, it is hoped that it can help the Regional Secretariat Apparatus Development Section at the Regional Secretariat Organization Bureau of South Sumatra Province in carrying out guest data management which carries out consultations both from the Sumatra Provincial Government agencies themselves and from city district governments in South Sumatra Province quickly, consistently and efficiently.